Hubungan antara Loneliness dan Perilaku Parasosial pada Wanita Dewasa Muda - Meidiati Sekarsari; Sri Fatmawati Mashoedi (Fakultas Psikologi Universitas Pancasila, 2009)
The rapid change in the entertainment world give us the opportunity to know the daily lives of the celebrity. With that opportunity, we could then feel that we know the celebrity and have relationship with that person, which can be called as parasocial. Some of the characteristics of an individual who have the tendency to do a parasocial behavior are having a lack of social interaction and low self-esteem. Both of those characteristics are also a personal characteristics as an individual who tend to experience loneliness. The aim of this research is to know if loneliness would be linked to the strength of one's parasocial behavior. The research used UCLA Loneliness Scale ver.2 to measure loneliness and Celebrity Attitude Scale to measure parasocial behaviors. The sample of this research was 84 young adulthood women in the age between 20-40 years old. The result of this research shown that there are significant positive relationship between loneliness and parasocial behavior in young adulthood women.